Internet and mobile technologies: addressing the mental health of trauma survivors in less resourced communities - J. I. Ruzek; C. M. Yeager (Cambridge Prisms: Global Mental Health, 2017)
Internet and mobile technologies offer potentially critical ways of delivering mental health support in low-resource settings. Much evidence indicates an enormous negative impact of mental health problems in low- and middle-income countries (LMICs), and many of these problems are caused, or worsened, by exposure to wars, conflicts, natural and human-caused disasters, and other traumatic events. Though specific mental health treatments have been found to be efficacious and cost-effective for low-resource settings, most individuals living in these areas do not have access to them. Low-intensity task-sharing interventions will help, but there is a limit to the scalability and sustainability of human resources in these settings. To address the needs of trauma survivors, it will be important to develop and implement Internet and mobile technology resources to help reduce the scarcity, inequity, and inefficiency of current mental health services in LMICs. Mobile and Internet resources are experiencing a rapid growth in LMICs and can help address time, stigma, and cost barriers and connect those who have been socially isolated by traumatic events. This review discusses current research in technological interventions in low-resource settings and outlines key issues and future challenges and opportunities. Though formidable challenges exist for large-scale deployment of mobile and Internet mental health technologies, work to date indicates that these technologies are indeed feasible to develop, evaluate, and deliver to those in need of mental health services, and that they can be effective.